(untitled) (Journal of the College of Basic Education, 2022)
Five coordination compounds, with general formula [M (HL)2Cl2]. xH2O, [M= Co(II), Ni(II), Cu(II), Zn(II) and Cd(II), x= 1 or 2 ] were prepared by reacting chloride salts of these metal with new azo-oxime ligand (E)-1-(4-((E)-(4,5-dimethyl-1-H-imidazole-2-yl) diazenyl) phenyl) ethanone oxime (HL), which was prepared by coupling of diazonium salt of 4-Aminoacetophenoneoxime with 4,5-diphenylimidazole. The heterocyclic azo-oxime ligand and its chelate complexes were identified by available techniques and the results showed that all chelate complexes have octahedral geometry